Terhadap Customer Satisfaction Melalui Purchase Decision dan Fashion Interest dalam Pembelian Handbag Imitasi (Studi pada Mahasiswi di Kota Malang) - Cindia, Ike; Rochman, Fatchur; Sunaryo, . (Universitas Brawijaya, Indonesia, 2016)
Abstract: This study was conducted to analyze the influence of reference groups on the purchase decision and fashion interest, then the influence of purchase decision and fashion interest on the customer satisfaction, and then the influence of reference groups towards customer satisfaction through the purchase decision and fashion interest. Research on the handbag became very exciting because imitation handbags booming and widely used in thecommunity, especially among female students in Malang. The sample in this study were taken by using the data collection method called purposive sampling. The number of samples that used were 115 respondents. The data obtained were analyzed by using PLS analysis technique (Partial Least Square) through the PLS software. Moreover, to test the hypothesis of the fifth, Sobel test was used to examine the relationship existing intervening variables in the hypothesis. The results showed that the reference groups have a significant positive effect on purchase decision and fashion interest. Then purchase decision and fashion interest also has significant positive effect on customer satisfaction. Furthermore, reference groups have a significant positive effect on customer satisfaction through the purchase decision and fashion interest.